Comparison of Causal and Non-causal Strategies for the Assessment of Baroreflex Sensitivity in Predicting Acute Kidney Dysfunction After Coronary Artery Bypass Grafting - Bari, Vlasta; Vaini, Emanuele; Pistuddi, Valeria; Fantinato, Angela; Cairo, Beatrice; De Maria, Beatrice; Dalla Vecchia, Laura Adelaide; Ranucci, Marco; Porta, Alberto (Frontiers in Physiology, 2019)
Coronary artery bypass graft (CABG) surgery may lead to postoperative complications such as the acute kidney dysfunction (AKD), identified as any post-intervention increase of serum creatinine level. Cardiovascular control reflexes like the baroreflex can play a role in the AKD development. The aim of this study is to test whether baroreflex sensitivity (BRS) estimates derived from noncausal and causal approaches applied to spontaneous systolic arterial pressure (SAP) and heart period (HP) fluctuations can help in identifying subjects at risk of developing AKD after CABG and which BRS estimates provide the best performance. Electrocardiogram and invasive arterial pressure were acquired from 129 subjects (67±10 years, 112 males) before (PRE) and after (POST) general anesthesia induction with propofol and remifentanil. Subjects were divided into AKDs (n=29) or no AKDs (noAKDs, n=100) according to the AKD development after CABG. The noncausal approach assesses the transfer function from the HP-SAP cross-spectrum in the low frequency (LF, 0.04-0.15 Hz) band. BRS was estimated according to three strategies: i) sampling of the transfer function gain at the maximum of the HP-SAP squared coherence in the LF band; ii) averaging of the transfer function gain in the LF band; iii) sampling of the transfer function gain at the weighted central frequency of the spectral components of the SAP series dropping in the LF band. The causal approach separated the two arms of cardiovascular control (i.e. from SAP to HP and vice versa) and accounted for the confounding influences of respiration via system identification and modeling techniques. The causal approach provided a direct estimate of the gain from SAP to HP by observing the HP response to a simulated SAP rise from the identified model structure. Results show that BRS was significantly lower in AKDs than noAKDs during POST regardless of the strategy adopted for its computation. Moreover, all the BRS estimates during POST remained associated with AKD even after correction for demographic and clinical factors. Noncausal and causal BRS estimates exhibited similar performances. Baroreflex impairment is associated with post-CABG AKD and both noncausal and causal methods can be exploited to improve risk stratification of AKD after CABG.